Effect of Service Quality, Price, and Facilities on Customer Loyalty to Uniqlo Surabaya - Haris Nur Mutazayid; Qausya Faviandhani; I Putu Artaya; Joko Suyono (Journal of World Conference (JWC), 2021)
Financial performance is used as a benchmark for the company to see how far the company can continue to survive and develop, and also to see the overall financial health of the company during a certain period. This research basically aims to measure the financial performance of PT. Garuda Indonesia for the 2019-2020 period by applying a profitability analysis using the Dupont method which is based on a return on equity analysis model. The Dupont method is used to analyze a company's profitability and return on equity by dividing performance into four components: net profit margin, total asset turnover, equity multiplier, and return on investment. PT. Garuda Indonesia is the number one and largest national airline in Indonesia with services and facilities that meet world standards. In 2019, airlines were affected by the Covid-19 Pandemic era which caused a global financial crisis. The results found that the financial performance of PT. Garuda Indonesia in 2019-2020 tends to decline in net profit margin, equity multiplier, and return on investment. Meanwhile, the return on equity showed a figure of -7.65% and in the last year it jumped high by 127.46% where the company was at a loss due to low equity due to excessive debt.